Treatment of hypoglycemia during prolonged physical activity in adolescents with type 1 diabetes mellitus - Fumanelli, Jennifer; Franceschi, Roberto; Bonani, Monica; Orrasch, Massimo; Cauvin, Vittoria (Acta Biomedica Atenei Parmensis, 2020)
Background: management of children with type 1 diabetes (T1DM) during physical activity includes intensive blood glucose monitoring and proper insulin and nutritional adjustments in order to prevent hypoglycemia. Regarding the treatment of hypoglycemia during physical activity, different types of rapid acting carbohydrate (CHO) can be used and recommendations are still debated.Aim of the work: compare the response to three types of frequently used rapid acting CHO to correct hypoglycemia during prolonged aerobic exercise. Subjects and Methods: 21 subjects with T1DM, aged 12-16 years, agreed to be recruited in the study. All participants took part in a trekking camp for 5 days, with 70 Km itinerary. A “flash monitoring” device was put on every participant and insulin and nutritional adjustments were done according to a protocol. Subjects have been randomized into three different groups: group 1 had to correct hypoglycemia with 0.3g/Kg of a glucose preparation; group 2 used sugar fondant candies; group 3 used fruit juice.Results: no significant differences were highlighted among the three treatments in terms of time spent in hypoglycemia, rise in blood glucose levels and number of hypoglycemic events after correction of hypoglycemia.Conclusions: our results suggest that 0.3g pro Kg of rapidly acting CHO in the form of glucose, sugar fondant or orange juice, effectively resolve hypoglycemia in children during aerobic prolonged physical activity.